Axin Facilitates Smad3 Activation in the Transforming Growth Factor β Signaling Pathway - Furuhashi, Masao (American Society for Microbiology, 2001)
Axin acts as a negative regulator in Wnt signaling through interaction with various molecules involved in this pathway, including β-catenin, adenomatous polyposis coli, and glycogen synthase kinase 3β. We show here that Axin also regulates the effects of Smad3 on the transforming growth factor β (TGF-β) signaling pathway. In the absence of activated TGF-β receptors. Axin physically interacted with Smad3 through its C-terminal region located between the β-catenin binding site and Dishevelled-homologous domain. An Axin homologue, Axil (also called conductin), also interacted with Smad3. In the absence of ligand stimulation, Axin was colocalized with Smad3 in the cytoplasm in vivo. Upon receptor activation, Smad3 was strongly phosphorylated by TGF-β type I receptor (TβR-I) in the presence of Axin, and dissociated from TβR-I and Axin. Moreover, the transcriptional activity of TGF-β was enhanced by Axin and repressed by an Axin mutant which is able to bind to Smad3. Axin may thus function as an adapter of Smad3, facilitating its activation by TGF-β receptors for efficient TGF-β signaling.